Karakteristik Kimia Biochar Limbah Bonggol Jagung pada Berbagai DurasiPirolisis: pH, Kapasitas Tukar Kation, dan C-Organik - Sara, Dirga Sapta; Sofyan, Emma Trinurani; Tridakusumah, Ahmad Choibar (Soilrens, 2026)
Biochar is a soil amendment material that can be produced through the pyrolysis of biomass,including corn cobs. This study aimed to determine the effect of pyrolysis duration on the chemical properties of corn cob biochar based on pH, cation exchange capacity (CEC), and organic carbon (Corganic) content. The study was conducted from May to July 2026 using a pyrolysis reactor at a temperature of 400 °C with four pyrolysis durations: 3 h (P1), 4 h (P2), 5 h (P3), and 6 h (P4), with three replications for each treatment. The observed parameters were pH, CEC, and organic carbon content. The data were analyzed using analysis of variance followed by Duncan's Multiple Range Test at the 5% significance level when significant differences were detected. The results showed that increasing the pyrolysis duration increased the pH and organic carbon content of the biochar. The pH values were 8.12, 8.31, 8.53, and 8.66 for P1 to P4, respectively, while the organic carbon content increased from 62.40% to 71.80%. CEC increased from 32.53 cmol kg⁻¹ in P1 to 42.40 cmol kg⁻¹ in P3, followed by a decrease to 40.40 cmol kg⁻¹ in P4. Treatment P4 produced the highest pH and organic carbon content, whereas P3 resulted in the highest CEC. Thus, pyrolysis durations of 5–6 hour produced favorable chemical characteristics of corn cob biochar based on the evaluated parameters.